2005
DOI: 10.1089/apc.2005.19.728
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Impact of Posttraumatic Stress Disorder and Comorbid Depression on Adherence to HAART and CD4+Counts in People Living with HIV

Abstract: Recent research suggests that the presence of posttraumatic stress disorder (PTSD) and depressive symptoms is independently related to abnormal hormone levels, inadequate medication adherence, and faster HIV disease progression. Although PTSD and depression occur comorbidly at high rates, the impact of both disorders on adherence and disease progression has not been examined. The present study examined the impact of PTSD and comorbid depression on CD4 cell counts and medication adherence in 58 male and 11 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
66
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 62 publications
7
66
2
1
Order By: Relevance
“…[13]. Recently, this pattern of association has also been found in studies of adherence that include biological measures associated with lower adherence, such as lower CD4 count [14] and detectable viral load [15].…”
mentioning
confidence: 62%
“…[13]. Recently, this pattern of association has also been found in studies of adherence that include biological measures associated with lower adherence, such as lower CD4 count [14] and detectable viral load [15].…”
mentioning
confidence: 62%
“…Ironically, this secrecy hinders uptake of treatment and of support services that can be provided by family members (Mill 2003). People who feel stigmatized or discriminated against are more likely to have poor health outcomes, socio-psychological problems, and suicidal thoughts , Reynolds, et al 2004, Bottonari, et al 2005, Katz and Nevid 2005, Sledjeski, et al 2005. Tackling HIV stigma will involve tackling perceptions and values towards sexuality and HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…For example, researchers have found that depression (Ammassari et al 2004;Kleeberger et al 2004;Sledjeski et al 2005) and low self-efficacy (Catz et al 2000;Godin et al 2005) contribute to low levels of reported adherence, and that having a good support system and positive attitudes (Catz et al 2000;Godin et al 2005) about medication taking foster adherence. While HIV adherence literature provides a good understanding of the personal and social variables that are most likely to play a role in ART adherence, the complexity of the interrelationships among these variables may be less well understood.…”
Section: Introductionmentioning
confidence: 99%